Assessment of livability in urban fabric: A comparative analysis - A. Fouladi; E. Sherafati Moghaddam; Y. Gholami (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: Livability, as a concept and approach, aims to reduce environmental, economic, and social problems in cities and communities based on their needs and capacities. This broad concept encompasses a variety of meanings in terms of physical, socio-cultural, economic, and environmental dimensions, both subjectively and objectively. Therefore, ensuring livability standards in the urban fabric is of considerable importance and necessity. The present study seeks to provide a basic understanding of the livability status in the city of Kashan.METHODS: To achieve this goal, employing a library method and a researcher-made questionnaire tool, 384 residents from seven old and five new neighborhoods were evaluated using a stratified (simple random) sampling method. The collected data were analyzed using SPSS software one-sample t-test analysis and structural equation modeling.FINDINGS: The results showed that the livability status in the new districts was better than the livability in the old ones. The findings reveal that overall livability in Kashan falls short of the desired average, with economic, cultural, and social aspects scoring the lowest. Environmental quality, on the other hand, was assessed as satisfactory. When comparing livability across old and new districts, the study found that newer districts have a higher overall livability compared to older ones. To further understand the factors influencing livability, the study prioritized the six dimensions of livability: infrastructure, politics, economy, environment, society, and culture. The economic factor emerged as the most influential, followed by social and infrastructural factors. Within the economic factor, job opportunities were identified as the most impactful aspect, while social cohesion and physical infrastructure held the greatest importance within the social and infrastructural factors, respectively.CONCLUSION: Importantly, the study highlights the role of effective urban management in enhancing livability, particularly in addressing economic disparities, fostering social inclusion, and improving infrastructure. Strategic interventions, such as targeted economic development policies, community engagement programs, and infrastructure investments, are essential for enhancing Kashan’s livability and quality of life.